Education and University in the 1979 Constitution - McGregor, Felipe (1981)
The 1979's Constitution of Peru introduces significant changes in the recognition of the rights and obligations of people. In particular, the right to education underwent several changes in its formulation. In this sense, the objective of this paper is to analyze the advances in the legal regime of education. To this end, the Constitutions of 1979 and 1933 are examined to highlight the most relevant aspects of the changes introduced. This analysis will make possible to detail the constitutional articles that refer to education, as well as the advances achieved for universities and the challenges that appeared. The conclusion is that important advances have been made in the recognition of education, as well as in the expansion of universities.